Invasion of the Asian Ladybird Harmonia axyridis (Pallas, 1773) in the European Part of Russia - Zakharov, Ilia; Ruchin, Alexandr; Egorov, Leonid; Romanov, Denis; Sazhnev, Alexey (Frontiers in Conservation Science, 2021)
The natural range of the Asian ladybird Harmonia axyridis (Pallas, 1773) covers the territories of China, Mongolia, Korea, Japan, and Russia (Far East, Southern Siberia, and Altai). Since the early 1980's, the global invasion of H. axyridis began, first on the territory of the United States, from where the Asian ladybird spread to South America, Africa, and Europe. By 2016, this species occupied all of Western Europe with the exception of its northern and southern regions. Penetration of H. axyridis on the territory of the Russian Federation (Kaliningrad) was discovered in 2010, and since 2011, the species has spread to the Black Sea coast. This report presents our data on the distribution of Harmonia axyridis in central Russia, from its western borders, to the Volga River. The occupation of this huge territory by this species occurred mainly in the last 3 years−2018–2020. The rate of movement of the species on the territory of the European part of Russia is about 200 km/year.